2020
DOI: 10.22452/mjs.vol39no1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Thyroxine Hormone on Gonadal Maturation and Growth of Male Spiny Lobster (Panulirus Homarus)

Abstract: The present experiments were designed to find the optimum dose of thyroxine hormone to enhance the gonadal maturation and growth of male spiny lobsters (Panulirus homarus). The maturation study used 30 male spiny lobsters divided into two treatments of weekly thyroxine hormone injections of 0 and 0.1 µg/g, respectively. Samples were taken to determine the following parameters: the gonadosomatic index (GSI), the anatomy, and the histology of the gonads. The growth study used 44 male spiny lobsters divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Further studies showed that injections of T4 promoted the development of embryos to hatching eggs depending on dosage, with the best results at 0.15 and 0.1 µg g -1 [15]. Adiputra et al [49] have shown that injection of T4 at a dose of 0.1 µg g -1 can induce a higher growth rate and better gonad development in male spiny lobsters of Panulirus homarus. Jayaprakas and Sambhu [50] found that thyroxine incorporated into a prepared diet promoted growth and feed utilization of white prawns of Penaeus indicus, being the most effective at 0.04 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed that injections of T4 promoted the development of embryos to hatching eggs depending on dosage, with the best results at 0.15 and 0.1 µg g -1 [15]. Adiputra et al [49] have shown that injection of T4 at a dose of 0.1 µg g -1 can induce a higher growth rate and better gonad development in male spiny lobsters of Panulirus homarus. Jayaprakas and Sambhu [50] found that thyroxine incorporated into a prepared diet promoted growth and feed utilization of white prawns of Penaeus indicus, being the most effective at 0.04 ppm.…”
Section: Discussionmentioning
confidence: 99%